Human cytomegalovirus utilises cellular dual-specificity tyrosine phosphorylation-regulated kinases during placental replication. (December 2018) - Hamilton, Stuart T.; Hutterer, Corina; Egilmezer, Ece; Steingruber, Mirjam; Milbradt, Jens; Marschall, Manfred; Rawlinson, William D.
Abstract: Introduction: Congenital cytomegalovirus (HCMV) infection may cause significant fetal malformation and in severe cases fetal and neonatal death. Fetal injury may be caused indirectly by the placental response to infection. Dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs) have recently been identified as critical kinases for HCMV replication. In this study we provide first evidence that DYRK1A and DYRK1B are utilised during HCMV placental replication. Methods: DYRK expression was investigated in AD169- and Merlin-infected TEV-1 trophoblast cells, ex vivo placental explants and naturally infected clinical placentae by immunofluorescence, western blot, co-immunoprecipitation and RT-qPCR. Results: HCMV-infected placental cells showed accumulation and re-localisation of DYRK1A and DYRK1B protein to areas of cytoplasmic virion assembly complexes and nuclear viral replication compartments, respectively. This accumulation was a result of upregulated DYRK1A/B protein expression with HCMV inducing up to a 5.3-fold increase in DYRK1A and up to a 4.7-fold increase in DYRK1B protein, relative to mock-infected TEV-1 cells ( p < 0.0001). Increased DYRK protein expression was correlated with DYRK1A/B mRNA upregulation, with HCMV-infected cells showing up to a 3.7-fold increase and 2.9-fold increase in DYRK1A and DYRK1B mRNA levels respectively ( p < 0.05). Protein-protein interactions were detected between DYRK1A/1B complexes and HCMV immediate early IE2p86, early pp65 and pUL44 and late pp150 proteins. Treatment of HCMV-infected TEV-1 cells and placental explants with DYRK inhibitors significantly inhibited HCMV replication ( p < 0.05) indicating these cellular kinases are required during HCMV placental replication. Conclusion: HCMV modulates cellular DYRKs during placental replication which may have implications for congenital HCMV pathogenesis and represent promising antiviral targets. Highlights: HCMV replication induces upregulation and relocalisation of placental DYRK1A/1B HCMV upregulation of DYRK1A/1B expression occurs at the mRNA level. DYRK1A/1B complexes interact with HCMV IE2p86, pp65, pUL44 and pp150 protein. Treatment of placental infection with DYRK inhibitors reduces HCMV replication.